2021
DOI: 10.3389/fpsyg.2021.607927
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression Symptom Level and Psychotherapy Use Among Music and Art Students Compared to the General Student Population

Abstract: Purpose: Previous epidemiological studies have shown higher levels of anxiety and depressive symptoms among professional musicians, compared to the general workforce. Similar findings have been observed for psychotherapy use among musicians. To date, large-scale investigations of prevalence rates among music and arts students are lacking.Methods: Eight hundred and eighty students from music and arts institutions and faculties were derived from a national health student survey for higher education in Norway (th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
0
19
1
Order By: Relevance
“…The negative changes in music students’ mental health between the beginning of their studies and the third or fourth years of study (Rosset et al, 2022) have already been documented. While there are some data on music students’ use of psychotherapy and counseling in Norway and the United States (Land, 1979; Vaag et al, 2021), we found no published data on the extent to which music students seek and attend counseling or on why they do so. Furthermore, no publications (to our knowledge) have yet reported longitudinal data collected in a higher education institution or discussed them relative to all enrolled students for a better understanding of trends over time.…”
contrasting
confidence: 65%
See 1 more Smart Citation
“…The negative changes in music students’ mental health between the beginning of their studies and the third or fourth years of study (Rosset et al, 2022) have already been documented. While there are some data on music students’ use of psychotherapy and counseling in Norway and the United States (Land, 1979; Vaag et al, 2021), we found no published data on the extent to which music students seek and attend counseling or on why they do so. Furthermore, no publications (to our knowledge) have yet reported longitudinal data collected in a higher education institution or discussed them relative to all enrolled students for a better understanding of trends over time.…”
contrasting
confidence: 65%
“…When compared to nonmusicians, music students reported taking less responsibility for their health and stress management, lower usage of coping strategies, poorer sleep quality, worse health overall, and higher rates of anxiety, depression, and MPA (Araújo et al, 2017; Robson & Kenny, 2017). However, there is contradictory evidence as to the extent to which musicians seek treatment for psychological issues (Vaag, Bjorngaard, & Bjekeset, 2016; Vaag et al, 2021; Wristen, 2013). The predictors of MPA include depression, being female, having experienced a breakdown while performing music (Robson & Kenny, 2017), negative cognitions such as catastrophizing (Liston et al, 2003), trait anxiety, and fear of negative evaluation (Osborne & Kenny, 2008).…”
mentioning
confidence: 99%
“…For example, Vaag et al (2016) reported that, compared to the general population, professional musicians had more symptoms of anxiety and depression. It also appears that music students show a greater number of these symptoms compared to the general student population (Spahn et al, 2004;Vaag et al, 2021), in addition to lower levels of self-efficacy and self-regulation (Ginsborg et al, 2009), and psychosocial well-being (Panebianco-Warrens et al, 2015). Anxiety and depression are not only highly prevalent among music students, but their symptom burden is even higher than that seen among professional musicians (Kegelaers et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies suggest that particular groups are more likely to be affected by behavioral addictions, such as work/study addiction and/or EDs, for instance, musicians, actors, or dancers [27,39,40,45]. The reasons are the lifestyle, a demanding performance schedule, a shortage of privacy, peer pressure, stress, depression, and performance anxiety [38,40,46,47]. The study's objective was to examine the relationship between study addiction and eating disorders, and their individual effects on well-being.…”
Section: Introductionmentioning
confidence: 99%